Proceedings of First Mardi Workshop on Oil Palm Technology, Kuala Lumpur, June 19-20, 1974 - MARDI Workshop on Oil Palm Technology (1st : 1974 : Kuala Lumpur); Malaysian Agricultural Research and Development Institute (Serdang : MARDI, 1974)
50